Are farmers’ climate change adaptation strategies understated? Evidence from two communities in northern Ethiopian highlands - Adamseged, Muluken Elias; Kebede, S.W. (Elsevier, 2023)
Research and policy analyses of climate change adaptation in Africa are often centre to examine adjustments in agricultural operations. This mainly bases on a misconception that rural households merely depend on agriculture for their livelihoods. This research aimed at positioning livelihood (farm and non-farm activities) as the centre of climate adaptation strategies to better understand rural households’ adaptation strategic options and capacities, using two rural communities in the Northern highlands of Ethiopia. The result showed that rural households have broader options both in farm and non-farm strategies for combating adverse climate condition than previously reported. A strong and positive association are found between wealth indicators such as farm size (0.08) and productive assets (0.0917) with farm-level adaptation strategies such as short maturing crop and irrigation. Non-farm adaptation strategies (such as business activities and wage employment) are, mainly, influenced by household demographic characteristics such as age of the household head (0.01) and adult household size (0.09). This indicates that there is no specific adaptation strategy panacea for rural households. Rather, rural households use a mix of strategies to meet the particular agro-ecological settings (for farm-level adaptation strategies), and infrastructure and the location of the community, which enable to access market and other services (for non-farm adaptation strategies). Thus, national level climate policies and strategies need to be tailored to address the specific agro-ecology, and infrastructure of the local area and the socio-economic context of the households in the two communities. In this regard, the different levels of government and nongovernmental organizations should provide more adaptation measures on agricultural extension services, access to loans, roads, transport, market, knowledge and creation of wage employment and business opportunities in the vicinity of rural communities and its surrounding towns.